In-vitro Antioxidant and Cytotoxic Activities of Silver Nanoparticles of Mangiferin Isolated from Mangifera indica - Mahendran Sekar (Journal of Global Pharma Technology, 2019)
The present study aimed to synthesize mangiferin AgNPs and evaluate its in vitro antioxidant and cytotoxic properties. Mangiferin AgNPs was prepared using silver nitrate solution and characterized by SEM and Zeta potential measurement. In-vitro antioxidant and cytotoxic studies of mangiferin and its AgNPs were conducted by using DPPH and MTT assay method, respectively. The synthesized mangiferin AgNPs with particle size ranges from 25.30 - 40.79 nm. The charge of mangiferin AgNPs were confirmed by Zeta potential and found to be −33.7 mV. Mangiferin AgNPs showed 90.43 ± 1.90 % of inhibition at 500 µg/ml and the activity was well comparable with mangiferin in DPPH method. Mangiferin AgNPs exhibited significant reduction in cancerous cell growth when compared to Mangiferin in all the tested concentrations ranges from 10-100 µg/ml. This results representing that the mangiferin AgNPs was a capable nanocarrrier for distributing mangiferin to cancer cells. In future, mangifrin AgNPs will be further tested with other cancer cell lines to confirm its safety and effectiveness.